Penerapan Perawatan Kaki Dan Kuku Terhadap Peningkatan Sirkulasi Perifer Pada Penderita Critical Limb Ischemia (CLI): Application Feet And Nail Care Enhancement Of Peripheral Circulation To Fill A Need Safety Of Patients With Critical Limb Ischemia (CLI) - Nurfantri Fantri; Muhaimin Saranani; Iluh Iriani (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Background . Critical limb ischemia (CLI) is the most severe stages disease vessels blood chronic , oriented CLI management on effort to anticipate doing amputation by pushing a severe infection happens on wound and healing the wound easier. One wrong possible intervention done to increase peripheral circulation and prevent the occurance of amputation consequence on severe infection is circulation maintenance. Purpose Describe feet application and nail care _ enhancement of peripheral circulation to fill a need safety of patients with Critical Limb Ischemia (CLI) . Method : This is a descriptive study uses a study case approach with a Nursing process approach . Subject of the study was one participant . Results the client felt painful on the feet , it started by feeling numb and cold on her left toes, then purple spots and several days later the spots were changed to be black and widespread to her calf . cold acral, nursing diagnosis enforced impaired peripheral tissue perfusion. Nursing Intervention: feet and nail care, Evaluation: decreased pain scale, increased muscle strength, changed in acral temperature and no changed in capillary refill. Conclusion : Giving circulation maintenance on client Mrs. S with CLI (Critical Limb Ischemia) for 5 days management was effective because on the fifth day client said painful on her left lower extremity decreased so that she could move , and client said she felt comfortable and relax after washing and cleaning her feet using warm water , soap , body lotion and cuting her toenails. Keywords : CLI, foot care , peripheral circulation, pain